1999
DOI: 10.3354/dao037013
|View full text |Cite
|
Sign up to set email alerts
|

Gill lamellar pillar cell necrosis, a new birnavirus disease in Japanese eels

Abstract: Since the late 1980s, a birnaviral gill disease has been occurring in Japanese eels Anguilla japonica reared in warmwater ponds in western regions in Japan. Diseased eels mostly displayed marked formations of aneurysmal hematomas within gill lamellae and high mortalities. Histological examination revealed necrosis of pillar cells and subsequent aggregation of erythrocytes inside the lamellar capillaries, and proliferation of interlamellar epithelia onto the lamellae. Gastric gland cells were also necrotized. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…Electron microscopy (EM) revealed that EVE virions were non-enveloped polyhedrons with a diameter of 68 to 77 nm, only present in the cytoplasm of infected cells. EVE also resembled IPNV in terms of biological properties, such as polypeptide composition and the bisegmented double-stranded RNA genome (Nishimura et al 1981a, T. Sano et al 1981, Hedrick et al 1983a Lee et al 1999aLee et al , 2001.…”
Section: Eel Virus European Aetiologymentioning
confidence: 99%
See 4 more Smart Citations
“…Electron microscopy (EM) revealed that EVE virions were non-enveloped polyhedrons with a diameter of 68 to 77 nm, only present in the cytoplasm of infected cells. EVE also resembled IPNV in terms of biological properties, such as polypeptide composition and the bisegmented double-stranded RNA genome (Nishimura et al 1981a, T. Sano et al 1981, Hedrick et al 1983a Lee et al 1999aLee et al , 2001.…”
Section: Eel Virus European Aetiologymentioning
confidence: 99%
“…The EVE-like virus isolated by Ueno et al (1984) caused 40% mortality in juvenile A. japonica after intraperitoneal injection at 20 to 25°C. EVE/ PCNV caused about 70% mortality in A. japonica (~40 g) during a 21 d experiment at 25°C, after intramuscular injection (Lee et al 1999a). All inoculated eels showed aneurysmal haematoma formation in gill lamellae and stasis of gill filamental arteries, similar to natural infections, and it was possible to reisolate the virus from diseased gill filaments.…”
Section: Experimental Infectionsmentioning
confidence: 99%
See 3 more Smart Citations